Science for Segregation : Race, Law, and the Case against Brown v. Board of Education. - Jackson, John P. (Critical America., 2005)
In this fascinating examination of the intriguing but understudied period following the landmark Brown v. Board of Education decision, John Jackson examines the scientific case aimed at dismantling the legislation. Offering a trenchant assessment of the so-called scientific evidence, Jackson focuses on the 1959 formation of the International Society for the Advancement of Ethnology and Eugenics (IAAEE), whose expressed function was to objectively investigate racial differences and publicize their findings. Notable figures included Carleton Putnam, Wesley Critz George, and Carleton Coon. In an.